Corrosion behavior of AZ91 Mg-Alloy coated with AlN and TiN in NaCl and Hank’s solution - Mohd Rosli, z.m.rosli; Zainab , Mahamud; Jariah, Mohamad Juoi; Nafarizal, Nayan; Kwan, Wai Loon; Yusliza, Yusuf; Hairul Effendy, Maulud (2013)
Magnesium alloys create increasing interest in structural application where weight reduction is vast concern. However, its low corrosion resistance especially in atmosphere environment restricts their wide application. In this study, AlN and TiN were coated on AZ91 Mg alloy using PVD magnetron sputtering. AlN and TiN existence is confirmed via grazing angle x-ray diffraction (GA-XRD). The corrosion behaviors of uncoated and coated AZ91 Mg alloy in3.5% NaCl and Hank’s solutions were investigated using a potentiostat during electrochemical corrosion test. AlN and TiN coated samples showed better performance in Hank’s solution with TiN coated samples have the least corrosion rate (penetration rate=0.040mm/yr and mass loss rate=0.191g/m2d) in Hank’s solution. These create interest to further works on exploring the potential of coated AZ91 Mg alloy in biomaterial application.